“Who is Afraid of Cesare Brandi?” Personal reflections on the Teoria del restauro - Salvador Muñoz Viñas (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art, 2016)
For many years, Cesare Brandi’s Teoria del restauro has been one of the most influential works on heritage conservation theory in Southern Europe and in Latin America. However, it has shortcomings that are immediately apparent to the reader: firstly, it is extremely obscure; and secondly, it makes contradictory assertions. This makes the near-cult status that it has achieved all the more fascinating. One explanation for this status might be because the work is seen as a “fetish” or an “almost-biblical” text, and as such, its ability to inspire has become more important than its intellectual soundness.